Handling Analysis of Short Shot Defects From Stretch Blow Molding Machine On 330 Ml Bottle Case Study At PT. XYZ : Analisa Penanganan Terhadap Defect Short Shot Dari Mesin Stretch Blow Moulding Pada Botol 330 Ml Study Kasus di PT. XYZ - Nugroho, Wistyo Nugroho; Fahruddin, A’rasy (Universitas Muhammadiyah Sidoarjo, 2024)
Stretch blow molding is a manufacturing method used in making hollow plastic products using polymer plastic with rotational symmetry. This method, which has been popular since the 1970s, is usually used to make PET bottle products for soft drinks and mineral water to liquid detergent. In the production process of 330 ml plastic water bottles using a stretch blow machine molding with a pneumatic system, making products usingThis machine has factors that can affect the quality of the bottles produced. Size deviation (even distribution of bottle thickness and bottle slope) not in accordance with specifications resulting in bottles with white shoulders and flanged (shrinkage). The aim of this research is to optimize the settings stretch blow molding machine parameters to produce good quality 330 ml plastic water bottle product. The variables (predictors) chosen are: preblow (bar), preform temperature (ºC), and P1 point (mm).